Resiliência e tecnologias digitais móveis no contexto da educação básica: senta que lá vem a história - Cerqueira, Valdenice Minatel Melo de (2014)
This narrative-based work is attached to the line of research known as New Technologies in Education of Education Program: Curriculum from PUC - SP. This is a descriptive and qualitative-related study that evolved from the implementation of Dante Tablet program in Dante Alighieri School between 2011 and 2012. The overall objective of this work is to observe, describe and analyze the actions employed in the implementation of a program intended for the integration of information, communication, mobile and digital technologies into the curriculum of a school of basic education, while identifying the resiliencies arisen concerning this implementation. For this, we carried out analyses on documents that reveal the history and routine of the mentioned school, among them records of the institution s foundation, its Internal Regulations, accounts of meetings for training teachers, reports of students and teachers steering committees, notes of teaching practices, and questionnaires for teachers of tenth-grade secondary school and students of the Student Steering Committee. The journey to Paradise of the poet Dante Alighieri, described in the book "The Divine Comedy", was used as a metaphor of the methodological process. As to the narrative that supports this work, its development was conducted in a spiral manner, from the concept of Valente s spiral learning. In this paper, the idea of resilience, taken from Simpson and Tavares studies, refers to actions that provide the ability to overcome difficulties and adversities. In addition to these authors, the theoretical framework also comprehends Almeida with regard to issues on curriculum web and Freire over his view on education as an intervention in the world that enables change and transformation. Throughout the work, we identified four resilient actions that were predominant for the maintenance of Dante Tablet program, which are: the creation of the Student Steering Committee; the amplified use of Virtual Learning Environment (MOODLE); the identification, encouragement and enhancement of successful practices that favored aspects of students and teachers authorship; and the provision of a high-quality connection to the Internet, which allows activities involving since the simple ones, such as searching and selecting information, until those that promote students authorship and co-authorship as well as, in a collaborative way, the production and organization of knowledge through cloud computing. The verification of these actions was possible through some indicators that, established by Fullan, are called in this research vectors namely, need, clarity, complexity and quality. In addition to the identification of those resilient actions, another finding of this work was that the process of integration of digital technologies into curriculum should be designed and effected from a deep reflection and a broad dialogue, with the participation of each individual involved in the pedagogical task (in particular, teachers, students and administrators) so as to approach the subject from the perspective of a shared management of web curriculum, prioritizing an online integration of people, ideas, knowledge and cultures. Finally, the expectation is that this work can contribute to the debate on integration of mobile digital technologies into the curriculum within the Brazilian basic education